Koplo Dangdut Music in Getas Village, Tanjunganom District, Nganjuk Regency as Social Stratification - Sulistiana, Defi (Universitas Negeri Surabaya, 2025)
This research examines koplo dangdut music in Getas village, Tanjunganom subdistrict, Nganjuk district, as a form of social stratification. This study employs a descriptive qualitative approach using literature review, observation, interviews, questionnaires, and documentation. The findings reveal two formats of dangdut koplo music performances held in Getas Village: dangdut orchestras and electronic dangdut. The residents of Getas Village are familiar with and enjoy dangdut koplo music, which they use as entertainment. As a result, dangdut koplo music in Getas Village is used as a form of entertainment and as a means of social stratification. The factors that make dangdut koplo music a form of social stratification are occupation and economic status. Individuals from higher social strata invite dangdut orchestras to perform at social events to entertain guests and demonstrate their social status. However, those from lower socioeconomic backgrounds opt for an alternative by inviting dangdut koplo musicians to elevate their social status within the community.